Transformasi Sampah Kaleng Aluminium Menjadi Karya Bermanfaat untuk Memberdayakan Ekonomi Masyarakat: Transforming Aluminum Can Waste into Valuable Creations to Empower the Community Economy - FX Kristianta; Januar Fery Irawan; Satrio Budi Utomo (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The management of inorganic waste, particularly aluminum can waste, remains a significant challenge across many regions in Indonesia. The consumption of canned products continues to rise, yet the waste management systems in place have not kept pace with this growth. Used cans are commonly discarded as trash or sold to scrap collectors at low economic value. In reality, when properly processed, these materials can be transformed into high-value raw materials for creative products. The target beneficiaries of this program are economically productive household industries, which continue to face key constraints in two critical areas: production and marketing. To address these challenges in a practical and sustainable manner, this community engagement program has been designed to improve the efficiency of aluminum can waste utilization within household production systems. Our partners are home-based aluminum artisans who, despite their productivity, currently lack access to simple, appropriate technologies to process aluminum waste effectively. As a result, the proposed solution involves designing and implementing training programs to develop recycled stoves from aluminum cans. These stoves serve not only as innovative, marketable products but also as a contribution to climate change mitigation efforts.